A Multi-Method Analysis of Diversity, Equity, and Inclusion Websites of Fortune 500 Agricultural and Food Companies - Garrett M. Steede; Rebecca Swenson; Troy McKay (Journal of Applied Communications, 2023)
Each year, Fortune magazine publishes a list of the 500 largest corporations in the United States of America based on total revenue in the previous fiscal year. As successful companies, these organizations must prioritize diversity, equity, and inclusion (DEI) for a multitude of reasons. The purpose of this study was to determine how agricultural and food companies on the 2021 Fortune 500 list demonstrated a commitment to DEI efforts on their corporate websites. Thus, we analyzed the DEI website of each food and agricultural company listed on the 2021 Fortune 500 list. Quantitatively, most websites only required two clicks to access resources and information regarding how the company supports diverse audiences in the workplace when navigating from the main corporate website. Corporations should ensure DEI is a priority for and clearly communicate this on the website using definitions, statements, and employee resources on websites. Additionally, using visuals such as photos, videos, and graphics can improve communication in this space. For the qualitative portion of the study, we analyzed the use of executive and employee voices in communicating about DEI on the corporate landing page. Two themes emerged. Within the corporate theme came the work-to-be-done subtheme which addresses corporate DEI work as a work in progress. The second theme was the personal and professional theme which helps support the personal and professional wellbeing of employees and stakeholders. We offer suggestions for communicators and executives for communicating about DEI in the food and agriculture webspace and offer recommendations for future research
Keywords: Diversity; Equity; Inclusion; Corporate; Websites; CSR; Food; Agriculture